1986
DOI: 10.1002/1097-0142(19861015)58:8+<1915::aid-cncr2820581421>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional support in the cancer-bearing host: Effects on host and tumor

Abstract: Cancer patients have the highest prevalence of malnutrition of any group of hospitalized patients. The potential causes of this malnutrition are numerous, as elements of both starvation and stress are evident in the cancer-bearing host. The presence of the tumor alone may lead to reduced intake of nutrients and treatment modalities of surgery, chemotherapy, and radiation therapy further exacerbate nutritional deficits. It is clear that the tumor requires energy substrates to grow, and that these substrates are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

1990
1990
2006
2006

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(13 citation statements)
references
References 76 publications
0
13
0
Order By: Relevance
“…However, later randomized controlled studies have suggested that aggressive nutritional therapy has no impact on tumor response, toxicity, or survival [1,9]. Moreover, one animal study showed that aggressive nutritional therapy could significantly increase tumor growth [20]. It is widely recognized that the outcome measures of aggressive nutritional therapy for patients with advanced cancer should also include the patients' overall quality of life [14].…”
Section: Introductionmentioning
confidence: 99%
“…However, later randomized controlled studies have suggested that aggressive nutritional therapy has no impact on tumor response, toxicity, or survival [1,9]. Moreover, one animal study showed that aggressive nutritional therapy could significantly increase tumor growth [20]. It is widely recognized that the outcome measures of aggressive nutritional therapy for patients with advanced cancer should also include the patients' overall quality of life [14].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, patients with advanced malignancy often suffer from malnutrition, which increases toxicity and decreases tumor responses to treatment, 2) and such conditions can be dose limiting in therapeutic regimens. A method for prediction of adverse reactions to chemotherapy is thus needed to avoid their occurrence.…”
mentioning
confidence: 99%
“…[71][72][73] Numerous tumor-bearing animal studies have demonstrated that tumor growth and metastasis can be significantly stimulated during periods of nutritional support. 74 Therefore, the ability of nutritional therapy to reduce morbidity and mortality in patients with cancer should be demonstrated before its widespread use is adopted in the clinical setting.…”
Section: Response To Nutritional Supportmentioning
confidence: 99%